Meningkatkan Hasil Belajar Siswa Melalui Model Pembelajaran Cooperative Integrated Reading and Composition (CIRC) - Muamarah, Nunik (Berkala Ilmiah Pendidikan Fisika, 2014)
Learning outcomes of student learning were low because teachers use models and methods that have not varied and students were less interested in learning. Therefore conducted a study purpose at describes the effectiveness of the learning model CIRC in improving student learning outcomes in class XI IPA MAN 2 Model Banjarmasin on the subject of static fluids. Specifically this study purposed to describe: (1) enforceability RPP, (2) social skills, (3) learning outcomes, (4) student interest. This research uses a model of action research Kemmis and McTaggart consisting of III cycles. The subject is a student of class XI IPA 2 MAN 2 Model Banjarmasin, on the subject of static fluids. The results showed that (1) the enforceability of the RPP cycle I, II, III categorized very good, (2) social skills of students has increased every cycle, by categories is good, (3) increasing student completeness of learning outcomes in the classical cycle I, II, and III was 76,67%, 87,50% and 93,33% (4) interest of students were seen from the dimensions of pleasure, interest, attention, and complicity by category is good. Be concluded that the learning outcomes of students of class XI IPA 2 MAN 2 Banjarmasin can be enhanced through learning model CIRC on the subject of static fluids. Â